2013
DOI: 10.1080/15287394.2012.755941
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of the Cytotoxic, Apoptotic, and Mutagenic Potentials of Isatin

Abstract: Isatin (1H-indole-2,3-dione) is a chemical found in various medicinal plant species and responsible for a broad spectrum of pharmacological and biological properties that may be beneficial to human health, as an anticonvulsant, antibacterial, antifungal, antiviral, and anticancer agent. The aim of the present study was to determine in vitro the cytotoxic, mutagenic, and apoptotic effects of isatin on CHO-K1 and HeLa cells using the MTT viability assay (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium brom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…It is commercially available as a yellow to red needle crystalline solid (molar mass: 147.13 g·mol -1 ; molecular formula: [3,4]. It has a broad range of therapeutic activities and the most common are as an anti-oxidant, anti-inflammatory and anti-cancer compound [5][6][7][8][9]. It has been reported as barely soluble in water (mole fraction solubility: 5.138 x 10 -5 at 298.15 K) [1].…”
Section: Introductionmentioning
confidence: 98%
“…It is commercially available as a yellow to red needle crystalline solid (molar mass: 147.13 g·mol -1 ; molecular formula: [3,4]. It has a broad range of therapeutic activities and the most common are as an anti-oxidant, anti-inflammatory and anti-cancer compound [5][6][7][8][9]. It has been reported as barely soluble in water (mole fraction solubility: 5.138 x 10 -5 at 298.15 K) [1].…”
Section: Introductionmentioning
confidence: 98%
“…In a previous study, we have demonstrated that isatin did not show a significant mutagenic effect on either Chinese hamster ovary cells (CHO-K1) or human cervical cancer cells (HeLa). However, the drug did reduce cell proliferation and promoted apoptosis in both cell lines (Cândido-Bacani et al 2013). In addition to these in vitro results, isatin was genotoxic and mutagenic in mice bone marrow and peripheral blood cells after 14 consecutive days of treatment, but not after acute injection (Cândido-Bacani et al 2011).…”
Section: Introductionmentioning
confidence: 94%
“…Since the 1980s, when researchers started testing indirubin in clinical trials for the treatment of chronic myelocytic leukaemia, studies have been conducted to evaluate the antitumour properties of this compound and its analogues, named indigoids (Bla zevi c et al 2015). Nowadays, several pieces of evidence suggest that these drugs present antiproliferative and proapoptotic activities against different types of tumour cell lines (Nam et al 2005;Perabo et al 2011;Singh et al 2012;Cândido-Bacani et al 2013;Song et al 2013;Ichimaru et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The current cytotoxic and apoptotic findings are consistent with the previous reports on the concentration and cell line dependent activities of isatin. 33,34) Apoptotic Analyses An evaluation of apoptosis of HeLa cells promoted by the isatin analogue 4d was carried out by using the dual staining method with Annexin V-fluorescein isothiocyanate (FITC)/propidium iodide (PI). The results showed that much greater change takes place in treated as compared to untreated cells (Fig.…”
Section: Structuresmentioning
confidence: 99%